Hybrid EMT and Phasor based MMC-HVDC Model for Advanced Power System Simulation - Raab, Alexander; Frauenknecht, Dominik; Luther, Matthias; Kuri, Ananya; Wellhoefer, Anatoli (IEEE Power and Energy Society General Meeting, 2022)
The objective of this paper is the implementation and comparison of a hybrid phasor-based (RMS) and electromagnetic transient (EMT) modular multilevel converter high voltage direct current (MMC-HVDC) model for advanced and detailed studies of large power systems. The general modeling approach for hybrid simulation of modular multilevel converters for HVDC applications with the corresponding control concepts is described. The HVDC model can be divided into AC and DC components with different simulation time steps and representation using network partitioning. The connected AC grids and converter models are considered in the phasor-based time domain, while the DC connection is simulated in the electromagnetic-transient time domain. The coupling of the models is established by the total energy control of the MMC. The hybrid approach is evaluated in comparison to an average MMC HVDC model in an EMT simulation. The results show the advantages of the hybrid model. The model can be simulated with comparatively low computational effort, while the DC transients can be represented in detail during disturbances.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Electromagnetic transient (EMT) simulation; High Voltage Direct Current (HVDC); Hybrid Model; Modular Multilevel Converter (MMC); Phasor-domain (RMS) simulation